Digital Transformation: Implementation of the “Gesit Media” Program through Interactive Socialization for Students of SDN Sidomulyo 1 Tuban - Pramesty, Meydiana Dyah; Susanto, Rika Yuli; Komania, Nasyiatul; Afifah, Rina Mei Zul; Arrohmaany, Sholahuddin Zulfan; Nuraida, Dede (Dimar : Jurnal Pengabdian Masyarakat, 2025)
Digital transformation in the world of education is an urgent need to equip students with 21st century skills. Community service through the "Gesit Media" program (Generasi Sidomulyo 1 Melek Digitalisasi Teknologi Global) at UPT SD Negeri Sidomulyo 1 Tuban aims to improve students' digital literacy, especially in the use of technology devices and applications. This program targets 6th grade students as preparation for higher education. The method used is interactive socialization involving direct demonstrations of the use of belajar.id accounts, introduction to artificial intelligence (AI), use of Google Drive for online storage and collaboration, and graphic design training using Canva. The results of the activity showed high enthusiasm from students in understanding and applying digital technology in learning. In addition, collaboration with teachers and school operators played an important role in the smooth running of the program. This program succeeded in increasing students' awareness and skills in using digital technology ethically and productively, so that it is expected to be a provision for them in facing the challenges of digital-based education in the future.